PENGEMBANGAN MEDIA PEMBELAJARAN FUN THINKERS BOOK MATERI PERISTIWA ALAM YANG TERJADI DI INDONESIA DI KELAS V SEKOLAH DASAR - Mariatul Kibtiah; Nana Hendracipta; Encep Andriana (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This research aimed to develop fun thinkers book learning media on the topic of ”Peristiwa alam yang terjadi di Indonesia” at grade V of elementary school and to know the feasibility of the learning media. This research was research and development involving 6 steps: 1) problem analysis, 2) data information collection, 3) product design, 4) design validation, 5) product revision, and 6) product testing. The subject on this study were 10 students at grade V. The data were collected through interviews, quistionaire, the validity from material experts, language experts, media experts, and a quistionaire of students’ response. The result of this research was fun thinkers book learning media which consisted of two components: a book and the frame. The feasibility of the media was obtained from the result of the assesment from the experts. They were media experts, material experts, language experts, and quistionnaire of the students response with the average precentage of 90.8%, 97.5%,  81.82%, and 82.23% respectively. Based on these results, it was concluded that fun thinkers book learning media was feasible to be used as a learning media on the topic of ”Peristiwa alam yang terjadi di Indonesia”.